2007
DOI: 10.1111/j.1651-2227.2006.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Females born large for gestational age have a doubled risk of giving birth to large for gestational age infants

Abstract: Females, born LGA, have an increased risk to give birth to LGA infants, compared to mothers born not LGA. Maternal overweight increases this risk even further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 35 publications
2
35
1
3
Order By: Relevance
“…These results correspond with two Swedish studies in 2006 [24] and 2012 [25]. The retrospective epidemiologic study by Ahlsson et al [24] depict that females born…”
Section: Familysupporting
confidence: 74%
“…These results correspond with two Swedish studies in 2006 [24] and 2012 [25]. The retrospective epidemiologic study by Ahlsson et al [24] depict that females born…”
Section: Familysupporting
confidence: 74%
“…Additionally, it has been shown that both maternal insulin resistance and the maternal total glucose production rate (GPR) are associated with fetal growth [24,29]. Prepregnancy body mass index (BMI) and BMI in late gestation are also related to infant birth weight [24,30]. …”
Section: Introductionmentioning
confidence: 99%
“…Dies ist unabhängig vom ihrem ErwachsenenBMI und könnte damit ein ursächliches Ele ment sein für die ansteigende Adipositasepidemie [22].…”
Section: Langfristige Gesundheitliche Konsequenzen Für Das Kindunclassified
“…Eine randomisierte und kontrollierte Studie [27] wurde mit gesunden Frauen durchgeführt und bestand in einem zu Hause durchgeführten Ausdauertrainigsprogramm auf dem Fahrradergome ter gegenüber einer Kontrollgruppe (unterschiedlicher Fitnessgrad, unterschiedlicher BMI: [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Von der 20.…”
Section: Effekte Und Mögliche Gefahren Durch Körperliche Aktivität (Ka)unclassified